Addressing voltage decay in Li-rich cathodes by broadening the gap between metallic and anionic bands - Jicheng Zhang (Nature Portfolio, 2021)
Voltage fade is a critical issue for Li-rich transition metal oxide cathode. Here, the authors modulate the oxygen anionic redox chemistry and enlarges the gap between metallic and anionic states by constructing Li2ZrO3 slabs into Li2MnO3 domain in Li1.21Ni0.28Mn0.51O2 which fundamentally suppresses the voltage decay.